Isotherm and Kinetic Adsorption of Nitrogen–Doped Carbon for Remazol Brilliant Blue R Dye - Susanto Susanto; Handoko Desta Priadi; Mahhathir Muhammad; Agus Jalaluddin; Ricka Prasdiantika (Jurnal Teknik Kimia dan Lingkungan, 2026)
Industrial textile effluents containing Remazol Brilliant Blue R (RBBR) represent a significant environmental challenge due to their persistent nature and resistance to conventional biological treatment methods. This research explores the development of nitrogen-enriched carbon materials derived from palm oil empty fruit bunch (PEFB) cellulose as an effective adsorbent for RBBR elimination from contaminated water systems. The synthesized material was produced through thermal treatment at 700°C, enabling the formation of pyridinic nitrogen groups that improve surface alkalinity and create electron-rich active sites. Material characterization employed XRD, FTIR, and SEM-EDS techniques to evaluate structural and chemical properties. Laboratory-scale adsorption studies examined the influence of starting dye concentrations (100-500 mg/L) and reaction duration (10-120 minutes). Results demonstrated optimal fitting with the Freundlich isotherm model (qₘ = 434.78 mg/g) and pseudo-second-order kinetics, suggesting heterogeneous multilayer adsorption dominated by chemical bonding mechanisms. The proposed interaction mechanism involves electrostatic attraction between RBBR sulfonate functionalities and protonated pyridinic nitrogen sites under pH 6 conditions.